Prophylactic therapy for autoaggressive behavior in patients with paranoid schizophrenia with symptoms of depression - Dzeruzhynska, Наталія; Syropiatov, Олег; Zhyvaho, Христина (Psychosomatic Medicine and General Practice, 2020)
Introduction. Patients with depressive symptoms in schizophrenia are prone to recurrent autoaggressive behavior, including suicidal, in the first few months after withdrawal from a psychotic episode. There was no effect on the recurrent autoaggressive behavior of typical and atypical neuroleptics, mood stabilizers and others, especially in the presence of symptoms of depression. Our study aims to develop psychotherapeutic interventions according to selected targets, which will help the patient to control impulsive aggressive or autoaggressive behavior now and prevent recurrence of such behavior in the future, given that drug therapy does not guarantee such an effect. Materials and methods. The study involved 85 patients with paranoid schizophrenia by continuous sampling (out of 130 patients) and determining their possible inclusion in the study according to the inclusion / exclusion criteria. The following methods were used: clinical-anamnestic, clinical-psychopathological, pathopsychological, socio-demographic and mathematical statistics. All patients were examined on the scales PANSS, Calgary (CDSS), "Reasons for Life" (RFL), a questionnaire to determine normal behavior in stressful situations (Bass-Dark test) and methods for determining integrated forms of communicative aggression (Boyko V.V.). Results. According to the study plan, we conducted individual and group psychotherapy for patients of the main and control groups in the department during hospitalization. Given the beginning of quarantine measures (Covid-19), the number of participants in the groups was reduced to 6 people, taking into account the possibilities of the branch. Individual therapy continued as planned. None of the patients dropped out of the study. Group therapy included sessions of direct cognitive-behavioral therapy lasting 2 hours 2 times a week. Individual therapy was held 2 times a week depending on the patient's condition, the duration of the session was 50 minutes. Pathopsychological examination on selected scales was performed before and after the course of psychotherapy and after 3 months. It was noted that the individual approach to psychotherapy with the definition of targets of psychotherapeutic interventions can increase the motivation of patients to therapy, improves emotional regulation, provides opportunities to find constructive means of self-regulation. Conclusions. Psychotherapeutic work in case of autoaggressive manifestations should be aimed at the patient's values, individually focused on his needs, which are clarified with the help of appropriate questionnaires. Application of the proposed complex of preventive therapy (individual and group psychotherapy in the direction of CBT in combination with drug therapy) in patients with paranoid schizophrenia with symptoms of depression and autoaggressive manifestations allowed to achieve a significant sustainable and long-term improvement of the patient's condition both in the manifestations of autoaggression and in general indicators of aggression and emotional disorders.